2020
DOI: 10.1101/2020.04.16.044693
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gut Mycobiome Dysbiosis is Linked to Hypertriglyceridemia Among Home Dwelling Elderly Danes

Abstract: 24 25 26 Email addresses: 27 HFA fauzanahmad@ump.edu.my 28 JLC jcame@food.ku.dk 29 ŁK krych@food.ku.dk 30 BK bzo@food.ku.dk 31 WK wk@envs.au.dk 32 RLB r.bechshoeft@gmail.com 33 SR s.reitelseder@gmail.com 34 GWH grith.westergaard.hoejfeldt.01@regionh.dk 35 SBE se@food.ku.dk 36 LH l.holm@bham.ac.uk 37 KF karoline.faust@kuleuven.be 38 DSN dn@food.ku.dk 39 40 41 42 43 44 45 ABSTRACT 46 Gut microbial dysbiosis have been in the etiology of a number of diseases, yet 47 the presence of fungal communities and their pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 121 publications
1
9
0
Order By: Relevance
“…Fungal community increased with age in infancy but decreased when they grow up to young adults ( Figure 2 ). 88 However, gut mycobiota alteration in elder subjects was less reported, 114 and most of the older adults studied were reported with known diseases including hypertriglyceridemia (HG), 115 Alzheimer’s disease (AD), 51 , 116 and type 2 diabetes mellitus (T2DM). 19 In Denmark, gut mycobiome analysis was performed in 100 elderly participants (70 with normotriglyceridemia versus 30 with hypertriglyceridemia) aged 65–81 years by ITS 2 amplicon sequencing on their fecal samples.…”
Section: Gut Mycobiota In Elder Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fungal community increased with age in infancy but decreased when they grow up to young adults ( Figure 2 ). 88 However, gut mycobiota alteration in elder subjects was less reported, 114 and most of the older adults studied were reported with known diseases including hypertriglyceridemia (HG), 115 Alzheimer’s disease (AD), 51 , 116 and type 2 diabetes mellitus (T2DM). 19 In Denmark, gut mycobiome analysis was performed in 100 elderly participants (70 with normotriglyceridemia versus 30 with hypertriglyceridemia) aged 65–81 years by ITS 2 amplicon sequencing on their fecal samples.…”
Section: Gut Mycobiota In Elder Subjectsmentioning
confidence: 99%
“…Penicillium, Candida , and Aspergillus were the top three genera among the elderly Danes, and genus Penicillium was strongly correlated with the hypertriglyceridemia. 115 Another study on 17 older subjects (11 mild cognitive impairment versus 6 cognitively normal) with average age of 64.6 years showed that Saccharomyces, Candida , and Aspergillus were major fungal genera in their fecal samples through ITS 1 sequencing. Higher abundance of Botrytis, Kazachstania, Phaeoacremonium , and Cladosporium and decreased abundance of Meyerozyma at genus level were found in the gut of patients with mild cognitive impairment compared with controls.…”
Section: Gut Mycobiota In Elder Subjectsmentioning
confidence: 99%
“…Amplicon libraries were created using two-steps custom PCR protocols targeting the V4 region of 16s rRNA as described previously: 515fB (5′ GTGYCAGCMGCCGCGGTAA 3′) and 806rB (5′ GGACTACNVGGGTWTCTAAT 3′) [11]. Briefly, the 16S rRNA V4 region was amplified using OneTaq® 2X Master Mix (NEB, Ipswich, USA) from the extracted gDNA using the primer pair 515F-806R [1] containing a partial Illumina Nextera adapter in their 5' end. The PCR condition used was 94 o C -30 seconds followed by 30 cycles of 94 o C -15 sec, 50 o C -15 sec and 68 o C -30 seconds.…”
Section: Dna Extraction Library Preparation and Dna Sequencingmentioning
confidence: 99%
“…Microbiota is known as a microbial community that shares either commensalism, mutualistic or pathogenic relationships. Over the years, studies on the composition of gut bacteria have focused on human models [1], [2] with lesser attention on other kingdoms like animal, plant, and the environment. Recently, studies on mammals such as dogs and cats are getting highlights as these animals are kept as human beings' pets and inhibit the same living quarters.…”
Section: Introductionmentioning
confidence: 99%
“…The gastrointestinal tract (GIT) is an environment that hosts complex microbial ecosystems dominated by bacteria and other organisms such as fungus, Archaea, viruses and protozoa, collectively known as gut microbiomes [1]. The fungal community found in the GI tract is known as gut mycobiota, and like their bacteria counterpart, they have a profound impact on health and disease [2] by playing an important role in maintaining gut functioning and immune development [3], [4]. Gut microbiota is involved in energy harvesting, storage, and regulation of host metabolic functioning and is essential for the production and absorption of metabolites like short-chain fatty acids [5] and other metabolites necessary for health and survival [6].…”
Section: Introductionmentioning
confidence: 99%